La multiplication de matériel de plantation de qualité pour améliorer l’état sanitaire et la productivité des cultures: Pratiques clefs pour les bananiers et les bananiers plantain: guide illustre - Staver, Charles; Lescot, T. (Bioversity International, 2015)
This illustrated guide summarizes the key practices for producing clean planting material of banana with a high yield potential for smallholders, depending on the pests and diseases which are present. The guide is also designed to contribute to better planning of the propagation of planting material for rural development and disaster relief projects.